La edición incunable de las Comedias de Terencio impresa por Johann Rosenbach (Barcelona, 1498) - Díaz Burillo, Rosa M. (Euphrosyne, 2017)
Abstract This paper presents a philological analysis of the only early edition of Terence’s plays printed in the Iberian Peninsula: the incunable of Comoediae Terentii, and of the commentaries of Donatus and Calfurnio (on Heaut.), printed in Barcelona in 1498 by the printer Johann Rosenbach. The paper sets the edition in its cultural context and examines its relationship with other incunabula of Terence’s plays; it establishes close connections with a specific group of these. The collation lets us conclude that Rosenbach’s edition took as its model the edition printed in 1495 in Venice by Simon Bevilaqua.